2013
DOI: 10.1002/eji.201242918
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 inflammasome affects DNA damage responses after oxidative and genotoxic stress in dendritic cells

Abstract: The NOD-like receptor (NLR) family pyrin domain-containing 3 (NLRP3) inflammasome is a cytoplasmic protein complex that mediates inflammatory responses to a broad array of danger signals. The inflammasome drives caspase-1 activation and promotes secretion of the pro-inflammatory cytokines IL-1β and IL-18, and might also participate in other cellular processes. Here, we tried to identify new pathways regulated by the NLRP3 inflammasome in murine dendritic cells (DCs) in response to monosodium urate (MSU) crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 48 publications
1
43
1
Order By: Relevance
“…The study included only 7 cases with MYC/ BCL6-DH but, interestingly, 6 of them were non-GCB and had a tendency to better prognosis than cases with MYC/BCL2-DH, which occurs almost exclusively in GCB tumors. Previous reports on the prognostic value of MYC/BCL6-DH have been controversial, 5,8 but the findings in the current study suggest that MYC/BCL6 may have a different biological meaning than MYC/BCL2 in DH tumors. One intriguing aspect in the CopieBergman et al study is the better-than-expected outcome of patients with MYC alterations, independent of the translocated partner or subtype of DH lesions, compared with the poor outcome reported in the majority of previous publications.…”
contrasting
confidence: 74%
See 1 more Smart Citation
“…The study included only 7 cases with MYC/ BCL6-DH but, interestingly, 6 of them were non-GCB and had a tendency to better prognosis than cases with MYC/BCL2-DH, which occurs almost exclusively in GCB tumors. Previous reports on the prognostic value of MYC/BCL6-DH have been controversial, 5,8 but the findings in the current study suggest that MYC/BCL6 may have a different biological meaning than MYC/BCL2 in DH tumors. One intriguing aspect in the CopieBergman et al study is the better-than-expected outcome of patients with MYC alterations, independent of the translocated partner or subtype of DH lesions, compared with the poor outcome reported in the majority of previous publications.…”
contrasting
confidence: 74%
“…Several studies have shown that infective agents and microbial products can induce DSBs either directly or indirectly through reactive oxygen species (ROS). [3][4][5] Moreover, unrepaired DSBs activate the cytosolic DNA sensor stimulator of interferon genes, thus inducing the production of interferon alpha and interferon beta, which promote innate immune responses. [6][7][8] Pereira-Lopes et al broaden our knowledge of the physiologic functions of DDR in innate immunity, demonstrating for the first time that multiple macrophage functions are controlled by DDR, in particular, by the Nijmegen breakage syndrome 1 (NBS1) protein, the component of the MRN complex that is responsible for translocation of the MRN complex into the nucleus.…”
mentioning
confidence: 99%
“…Too high an NALP3 level could be dangerous for microglia by inducing pyroptosis, a caspase-1-dependent form of programmed cell death [50]. In line with this, Licandro et al [51] recently suggested that NALP3 modulates a number of signal pathways involved in DNA damage response and apoptosis. Finally, the most intriguing aspect of this study is the enhanced proliferation of in vivo primed, antigen-specific T lymphocytes in MG-MSC cocultures, that is, the increased antigen-presenting ability of microglia on MSC coculture.…”
Section: Microglia Activation and Effector Functionsmentioning
confidence: 93%
“…Additionally, studies conducted using monosodium urate (MSU) crystals in murine dendritic cells (DC) from Nlrp3 −/− mice suggest the role of inflammasomes in the disease process. DCs from Nlrp3 −/− mice respond differently to MSU or other ROS-mobilizing stimuli (rotenone and γ-radiation) compared to DCs from WT mice (Licandro et al, 2013). Furthermore, DNA fragmentation is markedly reduced in DCs from Nlrp3 −/− and Casp-1 −/− mice compared to those from WT mice.…”
Section: Inflammasomes In Human Pathological Conditionsmentioning
confidence: 99%